Declining idealism: A study of higher education teacher’s beliefs about grading decision making - Bambang Pratolo; Eko Purwanti (International Journal of Education and Learning, 2021)
This study aimed to unpack higher education teachers’ beliefs about grading decision making. A qualitative approach was employed in this study to answer the research question. In-depth semi-structured interview as the main data collecting technique was utilized to gather any information from higher education teachers. Four higher education teachers with different educational backgrounds and teaching experiences volunteered to be the participants. Three main themes were generated from the data i.e., the factors considered in grading decision making, the most challenging parts in grading, and handing students’ complaints about grades. This study indicates that developing assessment rubrics, discussing them with students, and documenting them in the learning contract may be effective strategies for teachers to remind the students of the course requirements to reach minimum criteria of mastery learning.